Farmer’s Knowledge, Perception, & Management of Major Diseases of Ginger in Palpa District, Nepal - Bhandari, Niraj; Subedi, Anuja; Giri, Hom Nath (Nepalese Horticulture, 2024)
Ginger, a high-value spice crop of mid-hill regions in Nepal, is ranked fourth in global ginger production. Palpa is one of the major ginger-producing districts of Nepal. The survey was conducted in the Ginger Block of Agriculture Knowledge Center (AKC), Palpa using a semi-structured questionnaire, key information interview, and focus group discussion on the knowledge and management of ginger disease. Out of 905 respondents, 90 ginger farmers from the Bagnaskali, Nisdhi, and Purbakhola rural municipalities were randomly selected for the study. Both primary and secondary data were collected and analyzed through computer software like the Statistical Package for Social Science (SPSS) and Microsoft- Excel including simple descriptive statistics, chi-square test, and independent t-test. Rhizome rot (Index -value 0.95), was reported as a major disease followed by Bacterial wilt, leaf spot, soft rot, and storage mold and disease severity occurs 3-5 months day after sowing (DAS). Most farmers adopted the cultural method instead of the chemical method despite a high literacy rate and had a significant association with the use of chemical pesticides at a 5% level of significance. Furthermore, training had found a significant association with farmers’ knowledge level of diseases at a 1% level of significance. Farmers had perceived a 31.58 % yield loss due to disease, 40% loss of income, and agriculture income had found a positive influence on the adoption of disease management. Thus, effective and efficient disease management methods should be adopted to hinder yield loss and control disease.